Ordem em Processo: investigando a forma urbana dos assentamentos informais - Guimarães, Carolina Jorge Teixeira (2024)
The phenomenon of informal settlements marks the reality of contemporary cities globally. Its definition requires in-depth exploration in order to address ambiguities and overcome stigmas. In Brazil, settlements have been the subject of study for over half a century. Despite progress, urban legislation still fails to recognize the reality of Brazilian cities (Maricato, 2002). There are many interventions and planning exercises that, by failing to recognize this reality, contribute to the perpetuation of poverty (Cardoso, 2007). Under urban and land tenure irregularities, informal settlements are labeled as disordered spaces, when in fact, they have an implicit "self-regulation" (Nisida, 2017). Acknowledging the existence of spatial organization in settlements means accepting the development of a particular order. Recognizing and discovering an order in areas that are incompatible with the notion of an ideal city, based on rationalist origins, is a complex challenge. Therefore, it is clear that in order to see informal settlements as spaces that produce order, new methodologies for representing these territories are necessary. This is because the act of representation involves choosing what to highlight in an object of infinite reality. The aim of this study is to investigate the order of the urban form of informal settlements, understanding it as a challenge in representing the reality of urban space. The research is defined as Design Science Research, as it is directly committed to the development of an investigative methodology, the proposed artifact. Among the methodological procedures, the main ones are bibliographic research and the process of schematic knowledge (Costa, 1998; Massironi, 1983). As part of the bibliographic study, the exploration of the field of urban morphology is highlighted as essential for studying ways of representing urban form. The work develops an integrated visual panel for investigating the order of urban form in informal settlements and applies it to a territory in Caucaia, in the Metropolitan Region of Fortaleza. This area was where the author worked for two years in a technical advisory role. The research aims to contribute to the debate on the phenomenon of informal settlements, positioning itself within the production circuit of the field of urban morphology. In light of another Brazilian city, apart from that regulated by legal instruments, order is in process.